Applications of Radiation Physics in Medical Imaging and Treatment: a Cross-Disciplinary Approach - Aia Haider Qahtan Al-Saowdy; Rawaq Taleb Hassan; Hijran Abdul-Razzaq Shatoul Rumi; Mohammed Raad Aziz Mohammed; Raghad Tahseen Mohammed hasan (American Journal of Botany and Bioengineering, 2025)
Radiation physics plays a crucial role in advancing medical imaging and therapeutic applications, yet gaps remain in optimizing its integration across disciplines. This study explores the intersection of radiation physics with medical imaging techniques such as X-ray, MRI, CT, and ultrasound, along with its applications in cancer treatment via radiation therapy. A literature-based analytical approach was employed to assess recent innovations and safety protocols in radiation-based medical interventions. Findings indicate that technological advancements, including AI-driven imaging analysis and precision-targeted radiation therapy, significantly enhance diagnostic accuracy and treatment efficacy. Results suggest that further interdisciplinary collaboration and regulatory frameworks are essential to balancing innovation with patient safety. The implications highlight the need for continuous improvements in radiation safety measures and integration of emerging technologies to optimize patient care.